Notes After Class: A Teachers’ Reflective Article About Working In Private And Public Scenarios: Notes After Class: A Teachers’ Reflective Article About Working In Private And Public Scenarios (Revista de Divulgación Shimmering Words: Research and Pedagogy E-Journal, 2024)
This reflective article is the result of the compilation of teachers’ narratives of their experiences while working in different stages of their careers in both public and private institutions. It is a qualitative study that uses grounded theory analysis to deep into the concerns and challenges they have faced while developing their teaching activities, and encourages discussion regarding stereotypes that pre-service teachers and teachers in general have internalized about public and private contexts. The data was gathered through written narratives and informal interviews with student-teachers while finishing their master’s degree in Language Teaching. The authors conclude that motivation -for both students and teachers- is an important factor for the success of the class, and that its procurance comes from multiple factors that can be associated with the type of institution where the teaching is developed.
Keywords: public and private education, teachers’ narratives, reflection on action, stereotypes.